A comparative of histological study between the kidney’s rabbits and guinea Pig - Dawood, Ghasaan A. (Journal of Kerbala for Agricultural Sciences, 2024)
The current study’s focus is on the different histological features in kidney between these species.There are six mature, healthyanimals for each type, rabbits, separated all of them have been prepared for examination in the animal house at College of Veterinary Medicine, Kerbala University.The animals were euthanized by I.M of diazepam (1 mg/1 kg)with ketamine (20 mg/1 kg). The samples were fixed in (10% ) formalin for 72 hours and dehydrated in alcohols after that, impregnation was done in paraffin. The embedded blocks are cut (7) μ thick and slices stained with (H &E) stain.The histological features of rabbit kidneys were renal corpuscles in cortex region less in number than renal corpuscles in guinea pig. In addition, the renal corpuscles in guinea pig had highly vascularized by glomeruli. The podocytes in guinea pig dense distribution inside of corpuscles. The Proximal tubule lined with simple cuboidal epithelial cells in both species but deferent in activity, the proximal tubules are in guinea pig had high brush border and appearance small in lumen, while in rabbit had large lumen. The Loop of Henle was consisted of the thin limbs.It is clear that feeding the histological results in kidneys of guinea pig its more activity than the kidneys in rabbits.